Biomechanical Assessment of Knee Laxity After a Novel Posterolateral Corner Reconstruction Technique. Issue 4 (March 2022) - Vivacqua, Thiago; Vakili, Samira; Willing, Ryan; Moatshe, Gilbert; Degen, Ryan; Getgood, Alan M.
Background: Different techniques to restore knee stability after posterolateral corner (PLC) injury have been described. The original anatomic PLC reconstruction uses 2 separate allografts to reconstruct the PLC. Access to allograft tissue continues to be a significant limitation of this technique, which led to the development of a modified anatomic approach utilizing a single autologous semitendinosus graft fixed on the tibia with an adjustable suspensory loop to enable differential tensioning of the PLC components. Purpose/Hypothesis: The purpose of this study was to compare the modified anatomic technique with the original anatomic reconstruction in terms of varus and external rotatory laxity in a cadaveric biomechanical model. The hypothesis was that both techniques would restore varus and external rotatory laxity after a simulated complete PLC injury. Study Design: Controlled laboratory study. Methods: Eight pairs of fresh-frozen cadaveric knee specimens were tested to compare the 2 techniques. Varus and external tibial rotation laxity of the knee were measured while applying 10-N·m varus and 5-N·m external rotatory torques at 0°, 30°, 60°, and 90° of flexion. These measurements were tested under 3 conditions: (1) intact fibular collateral ligament, popliteal tendon, and popliteofibular ligament; (2) complete transection of the fibular collateral ligament, popliteal tendon, and popliteofibular ligament; (3) after PLC reconstruction with either the modified (n = 8) or the original (n = 8) technique. Results: After PLC reconstruction, varus laxity was restored with no statistically significant differences from the intact condition after both reconstruction techniques. Similar outcomes were observed for external rotation in extension; however, in terms of the external rotation limit with respect to the intact joint, significant reductions of mean ± SD 4.1°± 6.3° ( P = .036) and 5.1°± 6.6° ( P = .016) were recorded with the modified technique at 60° and 90° of flexion, respectively. No significant effect was observed on the neutral flexion kinematics from 0° to 90° of flexion, and no significant differences were observed between reconstructions ( P = .222). Conclusion: Both PLC reconstruction techniques restored the normal native varus as compared with the intact knee. Although the modified technique constrained end-range external rotation at 60° and 90° of flexion, no differences were noted with neutral flexion kinematics. Care should be taken when tensioning in the modified technique so that the tibia is in a neutral position to avoid overconstraining the knee. Clinical Relevance: The modified technique may prove useful in situations where there are limited graft options, particularly where allografts are not available or are restricted.